Sensitivity and Specificity of Rapid Antigen Antigen Examination for COVID-19 Immunochromatography Method at the Dadi Regional Special Hospitals - Herman Herman; Nuradi Nuradi; Herdiansyah Herdiansyah; Herdiana Herdiana; Alfin Resya Virgiawan; M. Askar M. Askar (Jurnal Media Analis Kesehatan, 2023)
Currently COVID-19 is still in pandemic status so the transmission of this disease needs to be controlled. One of the government's efforts is to screen people suspected of COVID-19 with laboratory examinations using RT-PCR, but this is hampered by long test times. For this reason, the Rapid Antigen COVID-19 (RA COVID-19) immunochromatography (IT) method is used which is short in time and uses simple equipment. This research is a laboratory observational research which aims to determine the sensitivity and specificity of the RA COVID-19 method at RSKD Dadi, South Sulawesi Province. The research sample was 50 suspected COVID-19 patients being treated at RSKD Dadi, South Sulawesi Province and then nasopharyngeal swab samples were taken from these patients. The 50 swab samples were examined using the RA COVID-19 method and the Real Time Polymerase Chain Reaction (RT-PCR) method. Location The research was carried out at the RSKD Dani laboratory, South Sulawesi Province for 6 months (July-December 2022). The research results showed that the RA COVID-19 used at RSKD Dadi, South Sulawesi Province as a COVID-19 screening method for suspected COVID-19 patients had a sensitivity of 87% and a specificity of 97%. Conclusion: RA COVID-19 used at RSKD Dadi, South Sulawesi Province can be used as a screening method, but the results still need to be confirmed using the RT-PCR method